Outlandish Christendom: The Catholic Church in India and China - Friedrichs, J (Oxford University Press, 2018)
The Catholic Church, like Christianity more generally, has a marginal presence in India and China yet continues to face severe challenges. At least in part this is due to the fact that, in either case, Christianity is outlandish from a civilizational perspective. Despite these similarities, the challenges express themselves in different ways. In China, they mostly emanate from the state and express themselves as government restrictions. In India, they mostly emanate from society and express themselves as social hostilities. This difference is due to the fact that, in either case, Christianity is outlandish in a different way. In China, Christianity is foreign to a Han-centric imperial tradition: the state used to dominate religion and harness it for its purposes whenever the opportunity arose. In India, Christianity is foreign to a previously subaltern society: despite non-Hindu rule, Hindu elites have always been able to reproduce their hegemony. In both cases, the perceived foreignness of Christianity is reinforced by unpleasant memories of missionary activities during the colonial and imperialist period. When it comes to Catholicism, this is aggravated by the fact that the Church looks to an identifiable head (the Pope) and headquarters (the Vatican) located in distant Europe. Despite these challenges, there are also opportunities for Catholicism, and Christianity more in general. The final section discusses ways to navigate the challenges and pursue the opportunities.